Chiral Phosphoric Acid‐Catalyzed Enantioselective Synthesis of Pyrazole‐Based Unnatural α‐Amino Acid Derivatives. Issue 2 (28th October 2021) - Woldegiorgis, Alemayehu Gashaw; Han, Zhao; Lin, Xufeng
Abstract: An enantioselective synthesis of unnatural pyrazole‐based α‐chiral amino acid derivatives from the asymmetric reaction of N ‐aryl‐5‐aminopyrazoles with β, γ‐alkynyl‐α‐imino esters using a chiral spirocyclic phosphoric acid catalyst was developed. Using the established methodology, various pyrazole‐based α‐amino acid derivatives with tetrasubstituted carbon stereocenters were obtained in 67–98% yields and with 73–99% enantioselectivities. The NH2 functionality in the corresponding products enables further transformations to a chiral thiourea and a lactam. Abstract :